Rapid determination of chloride permeability of concrete through normal and accelerated chloride penetration testing - Santos, Alias Jady D.; Vidal, Nicholas Danielle O.; Plamenco, Dean Ashton; Caram, Rosabelle Louise, A. (Quezon City College of Engineering, University of the Philippines Diliman, 2018)
The normal salt ponding test has been widely used in recent years to evaluate the durability of cement-based materials. However, the duration of more than 60 days appropriate for salt ponding is considered rather time-consuming. In this study, the Accelerated Chloride Penetration Test (ACPT) is applied to accelerate the movement of chloride ions in the cement-based materials to reduce the duration of testing time. The chloride profiles are obtained from ponding test and ACPT. The distance penetrated by the chloride in specimens are measured from the profiles and compared. Based on the distance the chloride penetrated, the equivalent accelerated chloride migration time to the ponding time is obtained. The resulting accelerated penetration time needed for obtaining consistent values of the total amount of chloride penetration for cement-based materials equilibrated with 3-day, 6-day, 12-day, 24-day, 48-day, and 60-day ponding time are approximately 1 hr, 2 hr, 4 hr, 8 hr, 16 hr, and 20 hr respectively.
Thesis (Bachelor of Science in Civil Engineering)--University of the Philippines Diliman
Keywords: Concrete -- Effect of salt on; Concrete -- Corrosion